The Wiley Blackwell history of Islam - Salvatore, Armando; Tottoli, Roberto; Rahimi, Babak; ʿAṭṭār, Farīd-ad-Dīn; Patel, Naznin (Wiley Blackwell histories of religion, 2018)
Late antique beginnings (till ca. 661) -- The high caliphate (ca. 661-946) -- The earlier middle period (ca. 946-1258) -- The later middle period (ca. 1258-1453) -- Early modernity and civilizational apogee (ca. 1453-1683) -- Facing the global rise of European power (ca. 1683-1882) -- 7.colonial subjection and postcolonial developments (ca. 1882-present)